2011
DOI: 10.1136/thoraxjnl-2011-201054c.56
|View full text |Cite
|
Sign up to set email alerts
|

P56 Treatment of multidrug resistant tuberculosis: where are the guidelines for monitoring?

Abstract: curves. Cumulative TB rates were expressed as time after UK entry and time after GP registration and compared between immigrant subgroups stratified by WHO incidence in country of origin (150e499/100 000 or 500+/100 000) and age group at time of registration (<16, 16e35 or ¼36 years). The number needed to screen was calculated using an overall prevalence estimate of 25% IGRA positivity, with all cases occurring in this subgroup. Results 564 cases were recorded in 34 764 immigrants. The median (IQR) observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Patients experiencing injectable anti-TB drug from previous treatment courses had complaints of injection site pain and abscess. In addition, such patients frequently developed serious side effects, especially hearing impairment and renal function deterioration [27, 28]. Hence, PMDT team follow up renal function tests and hearing assessments before the initiation of treatment, frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Patients experiencing injectable anti-TB drug from previous treatment courses had complaints of injection site pain and abscess. In addition, such patients frequently developed serious side effects, especially hearing impairment and renal function deterioration [27, 28]. Hence, PMDT team follow up renal function tests and hearing assessments before the initiation of treatment, frequently.…”
Section: Discussionmentioning
confidence: 99%
“…1 A previous study identified that prior to the development of these monitoring guidelines the incidence of adverse effects associated with MDR TB medicines was high. 2 Objective To establish whether national guidelines for the monitoring of MDR-TB medicines at a tertiary centre are being adhered to. Results 9 patients with MDR-TB were included in the audit.…”
mentioning
confidence: 99%
“…1 A previous study identified that prior to the development of these monitoring guidelines the incidence of adverse effects associated with MDR TB medicines was high. 2 Objective To establish whether national guidelines for the monitoring of MDR-TB medicines at a tertiary centre are being adhered to.…”
mentioning
confidence: 99%